PEMBUATAN BIODIGESTER KERJASAMA DINAS LINGKUNGAN HIDUP SURAKARTA DI TPS3R RESPATA MOJO MAKMUR, KELURAHAN JEBRES, SURAKARTA - Burhanudin Burhanudin; Sriyanto; Arif Hidayat Purwono (Abdi Masya, 2026)
The problem of organic waste management in urban areas remains a major challenge, including in the City of Surakarta, which generates a high volume of waste daily. Most household waste is organic and originates in households; however, it is not yet optimally processed at the community level. Therefore, the application of simple yet effective technologies such as biodigesters represents a relevant solution to support waste reduction efforts while simultaneously promoting the use of alternative energy. This community service program aims to implement biodigester technology at the TPS3R RESPATA Mojo Makmur, Kodim 0735/Surakarta, Jebres Subdistrict, Jebres District, through collaboration between Sekolah Tinggi Teknologi Warga (STT Warga) Surakarta and the Surakarta Environmental Agency (Dinas Lingkungan Hidup/DLH). The activities include field surveys, the design and construction of the biodigester, operational training for TPS3R personnel, and initial usage assistance. The results indicate that the biodigester significantly reduces the volume of organic waste, produces biogas that can be utilized as supplementary energy, and generates liquid organic fertilizer with economic value. In addition, the program enhances personnel's knowledge and technical skills in managing waste using appropriate technology. Collaboration among educational institutions, local government, and the community has proven to deliver positive and sustainable impacts. This program is expected to serve as a model for organic waste processing that can be replicated in other areas of Surakarta and similar regions.